(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
A new species of Saurichthys, S. majiashanensis , is described. It comes from a series of marine vertebrate-bearing beds of the upper member of the Nanlinghu Formation outcropping in the large quarry at the top of Majiashan (Majia Hill) near Chaohu (Hefei City, Anhui Province, China). Its age is Middle Spathian (Olenekian, Early Triassic). This new species deeply differs from the several pre-Spathian species of Saurichthys mainly for having only two longitudinal scale rows together with a reduced grid-like structure for the neural elements in the vertebral column. Further derived characters are in the endoskeleton of the dorsal and anal fin, where radials articulate only to anterior lepidotrichia, the posterior ones being supported by the first scale from the caudal pedicle mid-dorsal and mid-ventral rows, deeply imbedded in the body. In addition, the haemal spines of the caudal region are much enlarged and reversed, with their distal parts pointing forwards. Though the skull is lacking, postcranial characters are enough to justify the erection of a new species. This new Saurichthys species, together with other few actinopterygians, can be considered as the oldest assemblage of the Triassic Middle Fish Fauna, which bloomed probably in the early Anisian and widespread especially all over the Tethys for the Middle Triassic and at least the Carnian in the Late Triassic. This new fish assemblage, together with some of the oldest marine reptiles, is considered as the beginning of the actual Triassic recovery among marine vertebrates.